PERKEMBANGAN SOSIAL ANAK USIA SEKOLAH DASAR PERSPEKTIF GENDER - Tuti Rezeki Awaliyah Siregar; Sukri Agustian (Universitas Islam Negeri Sumatera Utara, 2021)
Abstract: This study aims to examine how the role of gender in social development of elementary school age children. To get through this period, elementary school-age children need support from various parties in order to develop their abilities. Besides parents, children also need a social environment that can support their development. The existence of people around the child is one of the factors that can influence the development that is in it. Because in a social environment, children interact with all the good people who are the same age as him until adults who have ages far above. In supporting the social development of children, parents need to introduce the gender role that children will assume in the community so that they can be accepted in an environment of social interactionThe study in this study uses the library research method. The library research method is a study that takes facts from various scientific literature studies, such as books, journals, articles, magazines, internet, etc. Library research is usually philosophical and theoretical research because library research is not field research. The problems that exist in this research are analyzed and solved by referring to articles and articles that are closely related to the problem being studied.Keywords: Social Development, Basic Age, Gender